Possibilities for the quantitative determination of fat mixtures, starting from the complexometric index - García Villanova, R.; López Martínez, Mª. C. (Ars Pharmaceutica (Internet), 1970)
A new method is proposed for determination of mixtures of coco nut oil and olive oil or lard knowing the complexometric number of the mixtures wich is a linear function of the percentage.